2000
DOI: 10.1063/1.1150232
|View full text |Cite
|
Sign up to set email alerts
|

A compact ultrahigh-vacuum system for the in situ investigation of III/V semiconductor surfaces

Abstract: Articles you may be interested inStructure and morphology of the As-rich and the stoichiometric GaAs (114)A surface J. Appl. Phys. 95, 7645 (2004); 10.1063/1.1707212 GaAs(311) templates for molecular beam epitaxy growth: surface morphologies and reconstruction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Combining MBE with in situ STM has been accomplished in several systems [36][37][38][39]26]. The common approach is to custom build the MBE [38] and/or the STM [36,37], which limits the development of these systems to experts in the relating domain.…”
Section: Integrating Mbe and Stmmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining MBE with in situ STM has been accomplished in several systems [36][37][38][39]26]. The common approach is to custom build the MBE [38] and/or the STM [36,37], which limits the development of these systems to experts in the relating domain.…”
Section: Integrating Mbe and Stmmentioning
confidence: 99%
“…The common approach is to custom build the MBE [38] and/or the STM [36,37], which limits the development of these systems to experts in the relating domain. A different approach is to connect two commercially available MBE and STM facilities via a third custom built UHV chamber [39,26].…”
Section: Integrating Mbe and Stmmentioning
confidence: 99%
“…13 Samples with a typical size of about 5ϫ10 mm 2 were cut from a GaAs (1 1 3 ) B wafer ͑n-type, Si-doped, carrier concentration 1.4-4.8ϫ10 18 cm Ϫ3 , Wafer Technology͒. The samples were cleaned by several ion bombardment and annealing cycles.…”
Section: Shape Of Inas Quantum Dots Grown On the Gaasmentioning
confidence: 99%
“…Then the samples were introduced into a multichamber ultrahigh-vacuum system, which is described in detail elsewhere. 9 After oxide desorption samples were treated with several ionbombardment and annealing ͑IBA͒ cycles. SEM experiments carried out after this step showed that IBA is an effective method to remove the scratches from the last polishing.…”
mentioning
confidence: 99%